Тhе effect of ulrtasonic vibrations on the mechanical properties of nanocrystalline titanium - Bakai, К.S.; Bakai, S.А.; Kovtun, K.V.; Gorbatenko, V.M.; Shirokov, B.M. (Вопросы атомной науки и техники, 2018)
Mechanical properties of nanocrystalline titanium were studied under uniform confined compression with ultrasound oscillations of 20 kHz to clarify the way high frequency vibrations affect mechanical properties of nanocrystals. The nanocrystalline VT1-0 titanium of commercial purity used in the experiments was produced employing cryogenic grain fragmentation technique. This material has a broad distribution in grain size (20…80 nm) with the average size amounting to 40 nm. The amplitude of cyclic stress approaches 275 МРа. The high frequency vibrations are found to lower the yield stress and to initiate the formation of shear bands. With the deformation rate of 10⁻⁴ s⁻¹ the yield stress becomes 2.5 times lower, and the major shear band forms under the deformation of 0.11 which is 5.7 times lower than the true deformation before the major shear band formation without action of the vibrations. On increasing the deformation rate up to 10⁻³ s⁻¹ the consequences of high frequency vibrations impact weaken substantially. Для з'ясування питання про вплив високочастотних вібрацій на механічні властивості нанокристалів виконані дослідження механічних властивостей нанокристалічного титану при монотонному обмеженому стисненні під дією ультразвукових коливань з частотою 20 кГц. Використаний в експериментах нанокристалічний титан промислової чистоти ВТ1-0 отриманo методом кріогенної фрагментації зерен. Цей матеріал має широкий розподіл зерен за розмірами (20…80 нм) із середнім розміром, рівним 40 нм. Амплітуда циклічних напружень досягала 275 МПа. Встановлено, що високочастотні вібрації знижують поріг пластичності і ініціюють утворення смуг зсуву. При швидкості деформації 10⁻⁴ с⁻¹ поріг пластичності під дією вібрацій знижується в 2,5 рази, а головна смуга зсуву утворюється при деформації 0,11, яка в 5,7 рази нижче, ніж справжня деформація до моменту утворення головної смуги зсуву без впливу вібрацій. При збільшенні швидкості деформації до 10⁻³ с⁻¹ ефекти впливу високочастотних вібрацій істотно послаблюються. Для выяснения вопроса о влиянии высокочастотных вибраций на механические свойства нанокристаллов выполнены исследования механических свойств нанокристаллического титана при монотонном стесненном сжатии под действием ультразвуковых колебаний с частотой 20 кГц. Использованный в экспериментах нанокристаллический титан промышленной чистоты ВТ1-0 получен методом криогенной фрагментации зерен. Этот материал имеет широкое распределение зерен по размерам (20…80 нм) со средним размером, равным 40 нм. Амплитуда циклических напряжений достигала 275 МПа. Установлено, что высокочастотные вибрации снижают порог пластичности и инициируют образование катастрофических полос сдвига. При скорости деформации 10⁻⁴ с⁻¹ порог пластичности под действием вибраций снижается в 2,5 раза, а катастрофическая полоса сдвига образуется при деформации 0,11, которая в 5,7 раза ниже, чем истинная деформация до момента образования катастрофической полосы сдвига без воздействия вибраций. При увеличении скорости деформации до 10⁻³ с⁻¹ эффекты воздействия высокочастотных вибраций существенно ослабляются.